Penerapan Metode Problem Solving Cycle Dalam Perencanaan Dan Evaluasi Program Penyediaan Air Bersih Di Wilayah Rentan Kekeringan - Cristi Mokoagow; Aunike Pondaag; Christofan N Paath; Gabriel Wariki; Merien Shintia Radjakore; Angelika Tujuh; Jeremy Mewengkang; Augustinus Robin Butarbutar (STIKES Columbia Asia Medan, 2026)
Clean water is a basic human necessity that plays a vital role in public health and well-being. However, access to clean water remains a challenge in many drought-prone areas. This condition requires effective planning and evaluation to ensure the sustainability of clean water supply programs. This article aims to examine the application of the Problem Solving Cycle (PSC) method in the planning and evaluation of clean water supply programs in drought-prone regions. The study employed a literature review method by analyzing various scientific articles and relevant documents. Data were analyzed descriptively through identification, classification, and information synthesis. The findings indicate that PSC supports program planning and evaluation through the stages of problem identification, cause analysis, action planning, implementation, monitoring, and evaluation. Clean water supply programs contribute to improving community access to safe water and adequate sanitation, although several challenges remain, including limited resources, infrastructure management issues, and program sustainability. Therefore, PSC can serve as an effective approach to support the success of clean water supply programs in drought-prone areas.